PENGARUH PEMBERIAN SILIKAT TERHADAP SERAPAN FOSFOR, PERTUMBUHAN TANAMAN, KETAHANAN SERANGAN PENGGEREK DAN HASIL GULA DUA VARIETAS TEBU (Saccharum officinarum L.) - , hangger gahara mawandha, Prof. Dr. Ir. Tohari, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sugarcane is one of the important commodities in Indonesia. Silicate mineral that is one of the very abundant availability. Silicate is one nutrient that have benefits for plants as especially sugarcane. The research was conducted to reveal sugarcane response to the silicate dosage to absorption of phosphor, plant growth, resistance borer infestation, and yield of two varieties of sugar cane. This research was a field study that had been carried out at the PT Perkebunan Nusantara XIâs fields at Banter, Jatiroto District, Lumajang Regency, The Province of East Java Special Territory within November 2011 to Oktober 2012. The experimental design applied the split plot design. The first factors was the varieties of treatment consisting of 2 levels i.e. R579 and PS864. The second factors was the rate of silicate fertilizer consisting 5 levels, i.e. without silicate, 75 kg/hg of silicate fertilizer, 150 kg/ha of silicate fertilizer, 225 kg/ha of silicate fertilizer, and 300 kg/ha of silicate fertilizer. The collected data then were analyzed by analysis of variance (Anova) applying level of significance Î± = 5%. Whenever the significant differences among treatments were found, further analysis was carried out by applying a Duncan Multiple Range Test (DMRT) of Î± = 5%. The results showed that the dosage 150 kg/ha until 300 kg/ha of silicate fertilizer used has revealed increase silicate (Si) and phosphor (P) absorption in PS864 variety of plant cane. Silicate fertilizer used has revealed influence to the growth of root, stem, and shoot two varieties. The dosage 150 kg/ha of silicate fertilizer used has revealed prevent to stem borer and shoot borer infestation two varieties of plant cane. The dosage 300 kg/ha of silicate fertilizer used has revealed inhibit inversion of sucrose as well as increase content of phosphor in the sugarcane juice two varieties. The dosage 75 kg/ha of silicate fertilizer used has revealed increase the weight of plant cane for each hectare as well as the weight of crystal white sugar, but could not increase the content of sucrose in sugar cane.